Protecting Indonesian Children in Adapting Climate Change Based on Business and Human Rights Principles - Ezra, Tobias Binsar; Dewi, Chloryne Trie Isana (International Law Department, Faculty of Law Universitas Padjadjaran, 2024)
Based on research data, the climate change condition has increased globally. Indonesia is a part of this condition with over 100% increase in carbon emissions over the last 12 years. When it comes to the context of climate change, children have a different position as they become the most medically vulnerable group and are pivotal to Indonesia's future, demanding special attention. Previous research pointed out that one of the possible major contributors towards climate change and carbon emissions is companies in industrial and energy activities. With the availability of the child rights convention and national law, this article will answer the notion of whether the existing National Law in Indonesia is sufficient to prevent and protect the rights of Indonesian children in the future, along with an analysis of how business and human rights can push companies to comply and be held accountable in case of violation. The methodology that will be used in this research is the normative juridical method, creating a specific approach to laws and regulations based on data analysis. This article concludes that Indonesia will need to include more Climate change and Business and Human Rights aspects to handle the future implications of climate change impact. This article also concludes that to have a strong hard law system in Indonesia, an integration of International frameworks and Business and Human rights principles into the national law is essential.